BUDAYA ORGANISASI, EFEKTIVITAS ORGANISASI, DAN EKSISTENSI ORGANISASI DESA ADAT DALAM PEMBANGUNAN (KASUS DESA ADAT SESEH DAN DESA ADAT GERANA, KABUPATEN BADUNG, PROVINSI BALI) - Raka, Agung (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
Indigenous village as a community organization in Bali has its own character which is different than other organizations. Organization customary village has a goal: jagadhita sarwa sami Hita (Prosperous Spiritual Material), and sukerta Prahyangan governance, governance sukerta Palemahan Pawongan and sukreta governance. Organization customary village has a position that is very important and strategic in dealing with various problems of development. The research problems, a. How can organizational culture indigenous villages were able to maintain the existence of indigenous villages under construction in the traditional village and Gerana Badung Seseh? b. How can the effectiveness of customary village organizations in development in indigenous villages and indigenous villages Gerana Seseh Badung? c. How the existence of the traditional village and village customs Seseh Gerana under construction in Badung? Penelian qualitative research method used. Results pelitian, organizational culture, organizational effectiveness, and the existence of customary village organizations and indigenous villages Gerana Seseh almost no difference. But because of geographical differences that indigenous villages Seseh is located in the southern area (beach) which is the area of tourism, while the indigenous villages Gerana located in the northern area (mountains) is still an agricultural area so that the indigenous villages Seseh and indigenous villages Gerana there is little difference namely: (1) the traditional village Seseh: organizational culture is strong, the effectiveness of optimal organization, the leadership, the village board custom, fully held by the younger generation, the process of democratization, rationalization goes well, the activities of traditional village entirely handled together with impeccable manners (residents) indigenous villages. (2) The traditional village Gerana: strong organizational culture, optimal organizational effectiveness, leadership, traditional village board, has not yet held by the younger generation. The process of democratization, rationalization enough to run well, and the role of parents, traditional leaders still dominant with the traditional village activities. Keywords: Organizational Culture, Organizational Effectiveness, and the existence of the Organization of Indigenous Village, Seseh, Gerana Â